Workers experience guides Karaoke in Updating Status in Facebook as Interpersonal Relations and Personal Communication with Customers - Kiki Amelia Sari; Dra. Taufik Suprihartini, M.Si (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
The presence of information technology is rapid and practical nature can allow for changes in behavior or lifestyle. One of them is the development of information technology with the birth of social networks, namely Facebook. Karaoke guide also actively uses Facebook to update your status and communicate with customers. By using qualitative methods, this study aims to describe the